Education on Energy Efficient Underwater Light Emitting Diode (LED) Technology for Boat Lift Nets in Aceh Besar - Ricky Winrison Fuah; Imelda Agustina; M. Riswan; Heni Rusminda; Yeni Safitri Gurki; Raji Ufranal Halim; Alvi Rahmah; Ivonda Vicana Pandang; Nurhayati; Inda Mardhatillah; Zahra Afranisa; Putri Julia Mizulni; Maretty Twentyna Dolorosa; Rosi Rahayu; Ilham Zulfahmi (Bakti Cendana, 2026)
The coastal areas of Aceh Besar have high fisheries potential, but traditional fishermen using bagan boats in Gampong Lhok Layeun are facing declining catches due to technological limitations. The conventional lights used have limited light coverage and high fuel consumption. This service activity aims to improve the knowledge and skills of fishermen through education on energy-efficient underwater Light Emitting Diode (LED) technology as an alternative solution. The implementation method includes four stages: initial survey, socialisation, discussion, and evaluation and monitoring. The activity involved 25 participants consisting of fishermen, Panglima Laot, academics, and village officials. The results showed an increase in participants' understanding of underwater LED technology, with an average pre-test score of 57 increasing to 84 in the post-test. A total of 100% of participants expressed interest in adopting this technology, and showed high enthusiasm during the socialisation and discussion. This activity proves that participatory and educative approaches can strengthen traditional fisheries innovation at the local level.